2022
DOI: 10.1021/acsomega.1c06395
|View full text |Cite
|
Sign up to set email alerts
|

Mixed Nanocomposite Fertilizers Influencing Endophytic Symbiosis and Nutritional and Antioxidant Properties of Oryza sativa as a Sustainable Alternative for Commercial Fertilizers

Abstract: This study investigated the comparative effects of mixed nanocomposite (MNC) fertilizers as an alternative to commercial fertilizers (CFs) on endophytic symbiosis and nutritional properties of rice grains. We synthesized MNC fertilizers with different concentrations and characterized them by using scanning electron microscopy and Fourier transform infrared spectroscopy. The CF was applied as per the method followed by local farmers; however, for MNC fertilizers both foliar and soil applications were done. Comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 32 publications
(53 reference statements)
0
1
0
Order By: Relevance
“… 49 Our research group previously reported that D38 ( Chaetomium globosum ) biofertilization significantly promoted the growth of S. miltiorrhiza seedlings and increased the contents of tanshinones and phenylpropionic acids in S. miltiorrhiza roots. 50 , 51 …”
Section: Discussionmentioning
confidence: 99%
“… 49 Our research group previously reported that D38 ( Chaetomium globosum ) biofertilization significantly promoted the growth of S. miltiorrhiza seedlings and increased the contents of tanshinones and phenylpropionic acids in S. miltiorrhiza roots. 50 , 51 …”
Section: Discussionmentioning
confidence: 99%